Os processos administrativos sancionadores julgados pela CVM e sua relação com Compliance: um estudo com as empresas listadas no índice de governança corporativa - Smetana, Tais Bastos e Santos (2015)
This research addresses issues related to performance of the Compliance function and its relationship with the sanctioning administrative proceedings of the CVM. The objective was to examine whether common administrative processes with conviction are linked to the compliance department of the accused. The CVM regulates the market through regulations, those who do not comply are condemned in administrative proceedings. The methodology consists of an exploratory research through the mining of secondary data sources in the public domain, CVM and BM&F. It was analyzed the menu of 846 cases (ordinary and summary proceeding) separately. To examine whether the convicted companies belong to the New Market; mined the classification of companies in the new market available in the database of BM&FBovespa. Raising skills and compliance function, based on the theoretical foundation available in bibliographies it was conducted. Finally, it was concluded that the incentive socially good behavior reduce market distortions and prevent illegal practices, of 550 ordinary sanctioning administrative proceedings condemned related to compliance, only 24 (4%) companies listed are in New Market, Level1, Level2 and Bovespa More, and 526 (96%) are the traditional market, companies with a compliance program act preventively and thus focus less on administrative processes. Urges point out that corporate governance is a set of mechanisms of incentives and controls, internal and external, aimed at minimizing the costs of the problem of agency. Thus, the Compliance area is inserted into the corporate governance context, it is a control mechanism created by companies to ensure compliance with regulatory requirements and provide transparency in business. The Compliance of Brazil has influence of international law as the UK Bribery Act 2010 and The FCPA (Foreign Corrup Practices Act). Both take into account the liability of legal entities based on internal controls and compliance procedures. Such procedures may mitigate or completely exempt the responsibility of the agents. Brazilian law Anti 12.846 / 2013 to create the leniency agreement, equivalent to an award-winning snitching also softens, its own way, the liability of legal entities. Therefore, companies that have an effective program of Compliance has a mitigating effect on corrupt practices